The classic metal‐sensing transcription factor MTF1 promotes myogenesis in response to copper. Issue 12 (5th November 2019) - Tavera‐Montañez, Cristina; Hainer, Sarah J.; Cangussu, Daniella; Gordon, Shellaina J. V.; Xiao, Yao; Reyes‐Gutierrez, Pablo; Imbalzano, Anthony N.; Navea, Juan G.; Fazzio, Thomas G.; Padilla‐Benavides, Teresita
Abstract : Metal‐regulatory transcription factor 1 (MTF1) is a conserved metal‐binding transcription factor in eukaryotes that binds to conserved DNA sequence motifs, termed metal response elements. MTF1 responds to both metal excess and deprivation, protects cells from oxidative and hypoxic stresses, and is required for embryonic development in vertebrates. To examine the role for MTF1 in cell differentiation, we use multiple experimental strategies [including gene knockdown (KD) mediated by small hairpin RNA and clustered regularly interspaced short palindromic repeats/CRISPR‐associated protein 9 (CRISPR/Cas9), immunofluorescence, chromatin immunopreciptation sequencing, subcellular fractionation, and atomic absorbance spectroscopy] and report a previously unappreciated role for MTF1 and copper (Cu) in cell differentiation. Upon initiation of myogenesis from primary myoblasts, both MTF1 expression and nuclear localization increased. Mtf1 KD impaired differentiation, whereas addition of nontoxic concentrations of Cu + ‐enhanced MTF1 expression and promoted myogenesis. Furthermore, we observed that Cu + binds stoichiometrically to a C terminus tetra‐cysteine of MTF1. MTF1 bound to chromatin at the promoter regions of myogenic genes, and Cu addition stimulated this binding. Of note, MTF1 formed a complex with myogenic differentiation (MYOD)1, the master transcriptional regulator of the myogenic lineage, at myogenic promoters. These findings uncover unexpected mechanisms by which Cu and MTF1 regulate gene expression during myoblast differentiation.—Tavera‐Montañez, C., Hainer, S. J., Cangussu, D., Gordon, S. J. V., Xiao, Y., Reyes‐Gutierrez, P., Imbalzano, A. N., Navea, J. G., Fazzio, T. G., Padilla‐Benavides, T. The classic metal‐sensing transcription factor MTF1 promotes myogenesis in response to copper. FASEB J. 33, 14556‐14574 (2019). www.fasebj.org